2017
DOI: 10.12932/ap-150217-0022
|View full text |Cite
|
Sign up to set email alerts
|

Antibody biosensors for the measurement and characterization of soluble CD147 molecules

Abstract: This method may be a beneficial tool for the determination of sCD147 isoforms for disease diagnosis and prognosis as well as for the definition of the cellular mechanisms of the immune system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The signaling pathways generated by this mAb that are responsible for the negative regulation of T cell activation are of interest for future investigation. In addition, by engaging the mAb MEM-M6/6, which reacts to CD147 Ig-like domain 2 (10,17), our results revealed that the functional epitope recognized by this mAb regulates T cell activation via CD147 expression on T cells and monocytes.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…The signaling pathways generated by this mAb that are responsible for the negative regulation of T cell activation are of interest for future investigation. In addition, by engaging the mAb MEM-M6/6, which reacts to CD147 Ig-like domain 2 (10,17), our results revealed that the functional epitope recognized by this mAb regulates T cell activation via CD147 expression on T cells and monocytes.…”
Section: Discussionmentioning
confidence: 76%
“…As the anti-CD147 mAbs M6-1E9, M6-1D4 and MEM-M6/6 inhibited T cell proliferation, to confirm that the inhibitory effect was caused by binding of the mAbs to its epitope on the CD147 molecule, a neutralization assay was performed using the recombinant CD147 molecule CD147-IgG ( 10 , 17 ). The binding ability of mAbs M6-1E9, M6-1D4 and MEM-M6/6 to CD147-IgG was first determined by indirect ELISA and found that all mAbs reacted to CD147-IgG (data not shown).…”
Section: Resultsmentioning
confidence: 99%